Penerapan range of motion terhadap gangguan mobilitas fisik dengan systemic lupus erythematosus - Dewi, Salma Setya; Diahsari, Armenia; Prasetyorini, Dwi (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Systemic lupus erythematosus (SLE) is a chronic, multisystem autoimmune inflammatory disease caused by the deposition of autoantibodies and immunological complexes. This condition is more common in reproductive women and has various clinical manifestations and prognoses. Purpose: To analyze the results of ROM tests in patients with systemic lupus erythematosus. Method: This study consisted of nursing assessment, diagnosis, intervention, implementation, and evaluation. Nursing care was provided in the West Aster Ward of Dr. Sardjito General Hospital, Yogyakarta, in July 2025. The study sample consisted of clients with systemic lupus erythematosus. Data collection techniques included interviews, observation, literature review, and physical examination. Results: Most respondents indicated moderate online game addiction (41.7%), experienced emotional disturbances (79.8%), and experienced very severe stress (20.0%). The Kendall Tau test showed a significant relationship between online game addiction and emotional disturbances (p=0.034; r=0.190) with weak strength and a positive direction. Furthermore, there was a significant relationship between online gaming addiction and stress levels (p=0.000; r=0.371), with moderate strength and a positive direction. Conclusion: Range of motion is expected to have an impact on Systemic Lupus Erythematosus patients who experience impaired physical mobility.   Keywords: Range Of Motion; Systemic Lupus Erythematosus.   Pendahuluan: Lupus Eritematosus Sistemik (SLE) adalah penyakit inflamasi autoimun multisistem kronis yang disebabkan oleh endapan autoantibodi dan kompleks imunologis. Kondisi ini lebih umum terjadi pada wanita yang produktif dan memiliki berbagai manifestasi klinis dan prognosis. Tujuan: Untuk menganalisis hasil tes ROM dengan lupus eritematosus sistemik. Metode: Penelitian ini terdiri dari pengkajian, diagnosa, intervensi, implementasi, dan evaluasi keperawatan. Lokasi pemberian asuhan keperawatan dilakukan di Ruang Aster Barat RSUP Dr. Sardjito Yogyakarta pada bulan juli 2025. Sampel penelitian yaitu klien dengan Systemic Lupus Erythematosus. Teknik pengumpulan data terdiri dari wawancara, observasi, studi pustaka, dan pemeriksaan fisik. Hasil: Sebagian besar responden menunjukkan kecanduan game online pada kategori sedang (41.7%), mengalami gangguan emosional (79.8%), dan mengalami stres sangat berat (20.0%). Hasil uji Kendall Tau memperlihatkan adanya hubungan bermakna antara kecanduan game online dengan gangguan emosi (p=0.034; r=0.190) dengan kekuatan lemah dan arah positif. Selain itu, terdapat hubungan bermakna antara kecanduan game online dengan tingkat stres (p=0.000; r=0.371) dengan kekuatan sedang dan arah positif. Simpulan: Range of motion ini diharapkan dapat berpengaruh pada pasien Lupus Eritematosus Sistemik yang mengalami gangguan mobilitas fisik.                 Kata Kunci: Range Of Motion; Systemic Lupus Erythematosus.